Anxiety and depression in sarcoidosis: the influence af age, gender, affected organs, concomitant diseases and dyspnea - Hinz, A.; Brähler, E.; Möde, et al., R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Heightened degrees of anxiety and depression are often found in patients suffering from sarcoidosis, but the reasons for that are unclear. Furthermore, age and gender differences of anxiety and depression in sarcoidosis have not been reported with reference to normative data. Objectives: The aim was to test age and gender differences of anxiety and depression in a large sample, and to examine the influence of affected organs, concomitant diseases and dyspnea. Methods: 1197 German patients diagnosed with sarcoidosis were examined, using the Hospital Anxiety and Depression Scale (HADS) and the MRC dyspnea scale. Results: Patients suffering from sarcoidosis were significantly more anxious and depressed than the general population. This effect was especially strong in young age groups. The number of affected organs, the number of concomitant diseases and the degree of dyspnea significantly predicted anxiety and depression scores in univariate analyses. Among the affected organs, muscles, nerves, and bones most significantly contributed to depression. Sleep apnea, restless legs syndrome, and arterial hypertension were associated with anxiety as well as depression. In multivariate analyses including age and gender, however, only dyspnea and the number of concomitant diseases remained predictors of anxiety and depression scores. Conclusions: The analysis of mental distress should take into account comparisons with normative values. Young patients deserve special social support. Dyspnea proved to be an important symptom in the prediction of anxiety and depression.